PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM), DIGITAL MARKETING, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI MEDIASI PADA KLINIK KECANTIKAN ZAP MANADO - Ayuwandira Humena; Stanss Levynna Hermien Verronica Joyce Lapian; Willem Johan Fredrik Alfa Tumbuan (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
This study aims to analyze the effect of Electronic Word of Mouth (E-WOM), digital marketing, and consumer trust on purchasing decisions, with brand image as a mediating variable at ZAP Beauty Clinic Manado. This research employs a quantitative approach using a survey method through questionnaires distributed to consumers. The data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results indicate that E-WOM, digital marketing, and consumer trust have a positive and significant effect on both brand image and purchasing decisions. Furthermore, brand image significantly influences purchasing decisions and serves as a mediating variable in the relationship between E-WOM, digital marketing, consumer trust, and purchasing decisions. These findings highlight the importance of digital marketing strategies, online consumer reviews, and trust-building in enhancing brand image and encouraging purchasing decisions. This study contributes to the development of marketing literature and provides practical implications for the beauty clinic industry in designing effective digital marketing strategies in the digital era.